KAJIAN RETORIKA BAGI PENYULUH DALAM MENINGKATKAN KUALITAS PEMAHAMAN AJARAN AGAMA HINDU - Untung Suhardi (Dharma Duta, 2020)
Explain about dharma isn’t easy. Discourse and personality of the new extension will touch the hearts of audiences when Religius Educator can communicate well and were able to give the example of the application of life in society . Therefore religius educator must have a communication competence that is rhetoric that touched the hearts of the audience so that they can work on improving the quality of understanding of religious teachings Hindus. The results showed that Dharma Wacana is informative and persuasive rhetoric into studies that must be mastered by religius educator. Therefore, the religius educator must pay attention to the discovery phase, the preparation of the message and remember the messages to be delivered. In addition, factors ethos, pathos and logos also affect the rhetoric of religius educator. Generally the religion educator utilizing the rhetoric in the delivery of Dharma Wacana, but in this case the extension is more focused on style and delivery Dharma Wacana in efforts to improve the quality of understanding of religious teachings Hindus.